Development of “RSA” Encryption Algorithm for Secure Communication - Guru, Abhishek; Ambhaikar, Asha (International Journal of Computer Sciences and Engineering, 2019)
In this paper there are modifications in the RSA algorithm by using more than four prime numbers in the combination of public and private key by using this factoring complexity of variables is increased. This is a new technique to provide max security for data over the internet. In this technique we are using more than four prime numbers which is not easily decomposed this technique provides more efficiency and reliability over the network. In this paper we try to increase the level of security by modifying the RSA Encryption Algorithm.